Análisis De Los Activos Corrientes Al Determinar La Rentabilidad De La “Empresa Grifine S.A” En Relación Del Apalancamiento - Muñoz Chaguay, Martha Fernanda (2019)
The objective of this research is to evaluate, during 2017 and 2018, the behavior of Liquidity and Leverage of the Company GRIFINE S.A. In this sense, the Inductive method was used when analyzing the different accounts of the Financial Statements of the company in a particular way to outline a general criterion of the company from the financial point of view, as Horizontal, Vertical Analysis were used as analysis instruments and the Analysis of Financial Ratios. When applying these analyzes, it was determined that the Company grew as a result of the Financing and that the liquidity has decreased and is below the industry. It is concluded that the company while increasing the liability decreases liquidity, increasing the risk